Ocean - Carbonates - Atmosphere - Cruise No. M96 - April 28 - May 22, 2013 - Pointe-à-Pitre (Guadeloupe) - Mindelo (Cape Verde) - Karstensen, Johannes (DFG-Senatskommission für Ozeanographie, 2014)
The scientific program of the R/V METEOR M96 expedition was devoted to a combination of atmospheric and oceanic observations. The survey route was oriented along a zonal section from the western to the eastern tropical Atlantic, nominally along 14.5 °N, while the section was started at 11°N (off Trinidad/Tobago). The atmospheric program addressed primarily processes related to aerosol transport, in particular the impact of Saharan dust. The long-range transport of dust from Africa to North and South America is an aerosol transport with far reaching consequences and with a strong impact on atmospheric processes, such as cloud formation and radiation balance in the tropical Atlantic. In particular the alteration of the aerosols during their westward transport is not well understood and was investigated during M96 with different methods. The oceanographic program was dedicated to estimating the meridional transport of mass, heat and freshwater in the tropical North Atlantic across 14.5°N. Moreover, the service of the three moorings at 16°N (the MOVE array, operational since 2000) was done. High-resolution hydrography (upper 250m; underway CTD) and currents (upper 1000m; ADCP 38kHz, 75kHz) were recorded end will enable mixed layer and air/sea interaction studies. The biological/biogeochemical program comprised incubation experiments, large volume in-situ pump systems, and underwater video profiling. : METEOR-Berichte